The Performance Analysis of Bank Syariah Mandiri with Maqasid Sharia Index Approach in the 2013–2017 Period - Nugroho, Anton Priyo; Puspitawati, Evi Setyorini; Andriansyah, Yuli (Universitas Islam Indonesia, 2022)
This study aims to analyze the performance of Bank Syariah Mandiri based on maqasid sharia using the maqasid sharia index (MSI) approach. The data was collected based on the bank’s reports from 2013-2017. Based on all performance indicators, the best performance of Bank Syariah Mandiri was in 2015, followed by 2017 and 2013. Maqasid sharia can be used as a reference in evaluating the performance of Bank Syariah Mandiri in the aspect of Islamic economics. The performance scoring effort can be maximized if the items or elements reported in Bank Syariah Mandiri financial statements can adjust to the maqasid sharia.